2018
DOI: 10.15517/rbt.v66i4.31908
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en la comunidad de peces por efecto del desarrollo costero en el Parque Nacional Huatulco (México)

Abstract: Coastal development and urbanization have increased the sediments that are washed from the land surface, producing adverse effects on the structure and functioning of coral reefs. The objective of this study was to identify the degree to which excessive sediments have disturbed the fish community in the coral reefs in the Maguey and Violin bays, located in the Huatulco National Park (Mexico). Fish samples were collected before and after disturbances produced by sediments associated with coastal development pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…Estudios previos en el Pacífico de Panamá y en otras regiones del POT han demostrado que los arrecifes sujetos a niveles altos de nutrimentos tienen una mayor abundancia de esponjas perforadoras las cuales se alimentan precisamente de materia y organismos en suspensión en la columna de agua (Enochs et al, 2021;Rose & Risk, 1985;Prouty et al, 2017). Por otro lado, la relativamente baja tasas de erosión por parte de peces y erizos encontrada en este estudio responde a las bajas abundancias de esos grupos en el área de estudio, lo que posiblemente está relacionado con las pesquerías locales y el desarrollo costero en la zona (Juárez-Hernández & Tapia-García, 2018).…”
Section: Discussionunclassified
“…Estudios previos en el Pacífico de Panamá y en otras regiones del POT han demostrado que los arrecifes sujetos a niveles altos de nutrimentos tienen una mayor abundancia de esponjas perforadoras las cuales se alimentan precisamente de materia y organismos en suspensión en la columna de agua (Enochs et al, 2021;Rose & Risk, 1985;Prouty et al, 2017). Por otro lado, la relativamente baja tasas de erosión por parte de peces y erizos encontrada en este estudio responde a las bajas abundancias de esos grupos en el área de estudio, lo que posiblemente está relacionado con las pesquerías locales y el desarrollo costero en la zona (Juárez-Hernández & Tapia-García, 2018).…”
Section: Discussionunclassified
“…However, as López-Pérez et al (2019) reported, information about its biodiversity is still scarce and fragmented. It is important to note that the coral communities in this region have undergone a variety of alterations due to both natural (Glynn and Leyte-Morales 1997;Lirman et al 2001;López-Pérez et al 2002 and anthropogenic factors (López-Pérez et al 2002, Granja-Fernández and López-Pérez 2008, Juárez-Hernández and Tapia-García 2018b. In particular, coastal development in the region has been reported to have rapidly increased over the past 20 years (Robles-Zavala and Chang-Reynoso 2018), and this has undoubtedly had an adverse impact on the coral communities and their biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…While Maguey Bay has been one of the most widely studied areas (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) (López-Pérez et al 2012Juárez-Hernández et al 2013; Juárez-Hernández and Tapia-García 2017), information about the ichthyofauna in it is incomplete, since there is no information for the year 2005. Additionally, it is important to mention that this bay experienced siltation disturbance in 2009 because of the entrance of sediments associated with coastal development projects, and this contributed to high mortality in corals and decreased abundance, number of species and diversity in fish communitites (Juárez-Hernández and Tapia-García 2018b).…”
Section: Introductionmentioning
confidence: 99%